I need help to solve this​
I need help to solve this​ - 1

Answers

Answer 1
Answer:

Answer:

2x+3(x+1.5)=12

Step-by-step explanation:

2x+3(x+1.5)=12


Related Questions

Which systems of equations have infinite solutions?
Based on the table below what is the relationship between tablespoons and cups
What is 4.06 X 20.1?
In 2000, there were 7689 weekly newspapers in the United States. This s about 94% of the number of weekly newspapers in the United States in 1960. How many weekly newspapers were there in 1960? Round to the nearest whole number.
Find the equivalent expression. 12a +6b A.2(10b + 4b) B.6(6a + b) C.2(6a + 4b) D.6(2a + b)

Jack buys a bag of 5 apples each equal in size he eat 1/2 of one Apple what fraction did he eat

Answers

You have 4(1)/(2) apples left. 
You have 5 whole apples, you took one whole apple out, which equals 4 whole apples left. Then with the whole apple you took out, you ate (1)/(2) of it.
 Jack ate (1)/(2) of an apple in 5 apples. 
If you say that Jack ate (1)/(2) of 3 apples, then he ate 1(1)/(2) apples. So there isn't any difference when he ate (1)/(2) of an apple.

Solve p= 10a+3b for a.

Answers

Answer:

a = p/10 - (3 b)/10

Step-by-step explanation:

Solve for a:

p = 10 a + 3 b

p = 10 a + 3 b is equivalent to 10 a + 3 b = p:

10 a + 3 b = p

Subtract 3 b from both sides:

10 a = p - 3 b

Divide both sides by 10:

Answer: a = p/10 - (3 b)/10

6/4 in reduced is 1 2/4 I need help now

Answers

Its actually reduced to 3/2. What you do is fin the greatest common factor in both numbers which is 2 and divide them by 2. Which will get you 2/3.

How do you solve this?

Answers

Answer:

a=4, b=144

Step-by-step explanation:

Let's take two random points of X and y and simplify the equation containing a and b; let's go,

Points (4,-5); (6,0)

For (4,-5)

-5= a -b/ (4 x4)

-5= a- b/16; -80= 16a - b[ by multiplying through by 16]

For (6,0);

0= a -b/ ( 6x6) ; 0=a- b/36

Multiplying through by 6, we have:

0= 36a-b; 36a=b;

So the modified equation of a and b are;

b=36a

b=16a+ 80[ modifying the derived expression moving b to the left]

So if we equate both expressions,

We have:

36a=16a+80;

36a-16a=80, 20a= 80; a= 80/20= 4;

a=4;

Substituting the value of a into any expression for b; we have

b= 36a= 36x4 =144

Hence a=4, b= 144

Y=a-b/x².

Using first column: x=1, y=140

140=a-b

Using last colimn: x=6, y=0

0=a-b/36, b=36a

140=a-b=a-36a=-35a

a=-140/35=-4

b=36a=36×(-4)=-144

Answer: a=-4, b=-144

Plzzzzzz help plzzzzz

Answers

(3+5)= 8
6*8=48
48/4=12
12

Light travels at 186,000 miles per second. Light takes about 11⁄3 seconds to travel from the earth to the moon. Calculate the distance between the earth and the moon based on the speed of light.

Answers

To answer the question above, multiply the speed of light with the time it takes to travel from earth to the moon. In this given, the product of the speed of light, 186,000 miles per second and 11/3 seconds is 682, 000 miles. Thus, based on the speed of light, the distance between the earth and moon is 682, 000 miles. 

Answer:

The correct answer is:

186,000 x 1 1⁄3 = 248,000 miles

Step-by-step explanation: